Characterization of a Lytic Bacteriophage vB_SurP-PSU3 Infecting Staphylococcus ureilyticus and Its Efficacy Against Biofilm - Kwon, Hyemin; Park, Seon Young; Kim, Min-Soo; Kim, Sang Guen; Park, Se Chang; Kim, Ji Hyung (Frontiers in Microbiology, 2022)
In response to the increasing nosocomial infections caused by antimicrobial-resistant coagulase-negative staphylococci (CoNS), bacteriophages (phages) have emerged as an alternative to antibiotics. Staphylococcus ureilyticus, one of the representative species of the CoNS, is now considered a notable pathogen that causes nosocomial bloodstream infections, and its biofilm-forming ability increases pathogenicity and resistance to antimicrobial agents. In this study, a lytic phage infecting S. ureilyticus was newly isolated from wastewater collected from a sewage treatment plant and its biological and antimicrobial characteristics are described. The isolated phage, named vB_SurP-PSU3, was morphologically similar to Podoviridae and could simultaneously lyse some S. warneri strains used in this study. The sequenced genome of the phage consisted of linear dsDNA with 18,146 bp and genome-based phylogeny revealed that vB_SurP-PSU3 belonged to the genus Andhravirus. Although its overall genomic arrangement and contents were similar to those of other members of the Andhravirus, the predicted endolysin of vB_SurP-PSU3 distinctly differed from the other members of the genus. The bacteriolytic activity of vB_SurP-PSU3 was evaluated using S. ureilyticus ATCC 49330, and the phage could efficiently inhibit the planktonic growth of the bacteria. Moreover, the anti-biofilm analysis showed that vB_SurP-PSU3 could prevent the formation of bacterial biofilm and degrade the mature biofilm in vitro. In an additional cytotoxicity assay of vB_SurP-PSU3, no significant adverse effects were observed on the tested cell. Based on these findings, the newly isolated phage vB_SurP-PSU3 could be classified as a new member of Andhravirus and could be considered an alternative potential biocontrol agent against S. ureilyticus infections and its biofilm.